China: Flows and effects of foreign direct investments - Antevski Miroslav (Međunarodni Problemi, 2012)
The paper analyses international flows and effects of a form of investment capital in case of China. Apart from the fact that they are a form of imports of foreign savings as a source of investment capital, foreign direct investments are rightly considered one of the potentially most significant factors of economic growth and international transfer of technology and knowledge. The empirical research has confirmed that such their potential, this also including the degree of its utilization, depends on the absorption capacity of the host country. China has recorded the greatest rates of economic growth in the last decade and its response to challenges of the global economic crisis has been the most successful. Also, China is the largest investment area in the world and the inflow of foreign direct investments is very significant, resulting from the attractiveness of the Chinese economy itself and measures for attracting foreign investments. The Chinese experience with the effects of foreign direct investment has been multiple, being both positive and negative, and it is very useful for other countries. On the other side, Chinese investments abroad have recorded fast growth rates, although their scope is still small in comparison to those of the most developed countries and they are present only in trade flows.